The IAB-INCHER project of earned doctorates (IIPED): A supervised machine learning approach to identify doctorate recipients in the German integrated employment biography data - Dominik Heinisch; Johannes Koenig; Anne Otto (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2019)
Only scarce information is available on doctorate recipients' career outcomes in Germany (BuWiN 2013). With the current information base, graduate students cannot make an informed decision whether to start a doctorate (Benderly 2018, Blank 2017). Administrative labour market data could provide the necessary information, is however incomplete in this respect. In this paper, we describe the record linkage of two datasets to close this information gap: data on doctorate recipients collected in the catalogue of the German National Library (DNB), and the German labour market biographies (IEB) from the German Institute of Employment Research. We use a machine learning based methodology, which 1) improves the record linkage of datasets without unique identifiers, and 2) evaluates the quality of the record linkage. The machine learning algorithms are trained on a synthetic training and evaluation dataset. In an exemplary analysis we compare the employment status of female and male doctorate recipients in Germany. – – Es gibt bislang nur wenige wissenschaftliche Studien, welche das Karriereauskommen von Promovierten in Deutschland untersuchen (BuWiN 2013). Daher bildet die empirische Evidenz zum jetzigen Stand für Absolventen keine hinreichende Informationsgrundlage, um eine wohlüberlegte Entscheidung für oder gegen eine Promotion zu treffen (Benderly 2018; Blank 2017). Administrative Daten zu individuellen Karriereauskommen könnten diese Informationslücke schließen. Jedoch sind die derzeitig verfügbaren Datenquellen in dieser Hinsicht unvollständig. In diesem Beitrag verknüpfen wir Daten zu Promovierten die im Katalog der Deutschen Nationalbibliothek (DNB) gesammelt wurden, mit den Integrierten Erwerbsbiografien (IEB) des Instituts für Arbeitsmarkt- und Berufsforschung (IAB). Wir verwenden Methoden des maschinellen Lernens, die es erlauben 1) Datensätze ohne eindeutige Identifier zu verknüpfen und 2) die Qualität des verknüpften Datensatzes zu bewerten. Die Algorithmen werden auf einem synthetischen Trainings- und Testdatensatz trainiert. In einer beispielhaften Analyse werden die Karriereauskommen von weiblichen und männlichen Promovierten miteinander verglichen.
Keywords: C81; E24; I20; 330; PhD; doctorate recipients; labour market trajectories; administrative data; record linkage; machine learning; supervised learning